"Okno na Barcza" (o powieści Juliusza Kadena-Bandrowskiego "Generał Barcz") - Goss, Łukasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2008)
General Barcz by Kaden-Bandrowski deals with the drama of power. The title character experiences a painful failure when the sacrifices he has made eventually turn out to bring him nothing but solitude. Barcz becomes a prisoner of politics. His everyday existance is limited to observing common people and their ordinary lives. Observing them through the window. In my article I am trying to show that Kaden used the motif of the window and the window frame and did it frequently and purposefully. When we take into accounts these symbols Kaden’s book appears to be not only a sophisticated political novel but a tragedy with a universal meaning.